Peningkatan Partisipasi Masyarakat dalam Pencegahan Korupsi untuk Meningkatkan Kualitas Pelayanan Publik di Desa: Peningkatan Partisipasi Masyarakat dalam Pencegahan Korupsi untuk Meningkatkan Kualitas Pelayanan Publik di Desa - Zakariya, Rizki (Komisi Pemberantasan Korupsi, 2020)
Village funds, which are routinely provided by the central government to villages, is prone to be a corruption subject. This study aims to describe the urgency of community participation and the efforts made to increase it in order to prevent corruption act. Thus, optimum quality of public services in the village can be improved. This research employs descriptive qualitative method with literature study. The results of this study urge the improvement of community participation in preventing corruption considering that the village huge economic potential is also standing side by side with high poverty rate. Furthermore, it is revealed that the vulnerability of corruption in the village occurred due to the lack of accountability and community participation in its financial management. Several efforts can be performed to increase public participation in preventing corruption such as by; 1) providing adequate access to program information and village budgets, 2) developing public awareness to participate in the program, 3) providing easy communication access to village officials, 4) optimizing village community organizations, and 5) optimizing the role of BPD.